Effect of the Amino Acids L-Methionine andD-Threonine on Calcium Lactate Pentahydrate Crystallization - KIRAN YILDIRIM, BERÇEM; SAYAN, PERVİZ; SARGUT, SİBEL (WILEY-V C H VERLAG GMBH, 2018)
The crystallization of calcium lactate pentahydrate was performed in the absence and presence of the amino acids L-methionine and D-threonine. The metastable zone width was measured as a function of concentration of amino acids and cooling rate. Fourier transform infrared (FTIR) analysis, scanning electron microscopy (SEM), filtration rate, and average particle size measurements were performed. FTIR results showed that all crystals formed in calcium L-lactate pentahydrate form, but crystals, which had a needle-like crystal structure in pure media, experienced a habit change in the presence of amino acids. The average particle size and the length-to-width ratio of the crystals increased in the presence of amino acids which appeared as reduction in mean specific cake resistance. The amino acids exerted enlargement effects on the metastable zone width.
Keywords: Calcium lactate pentahydrate; Crystallization; Essential amino acids; ADSORPTION; FRACTIONS; CRYSTALS